HARMONI DAN KETAHANAN KULTURAL DALAM TRADISI LISAN TYARKA DI KEPULAUAN BABAR, MALUKU BARAT DAYA - Lewier, Mariana (Masyarakat Indonesia, 2018)
This paper had been carried out to expose the cultural survivorship of oral tradition tyarka in Babar Archipelago, South West Mollucas as a cultural heritage based on its language aspect and performance, defense, and inheritance. The endurance or cultural survivorship of the linguistic aspect is expressed through the creativity of the production of poetic expression, while the performance aspect is examined based on the situation of the performance and audience participation. The defense and inheritance of the tyarka is revealed in connection with Babarâ€™s collective memory. This paper is the result of a qualitative research using an etnography method. The data were focused on the tyarka performance in Eastern Babar and Masela Island without neglecting the others in Babar Archipelago. By analizing the oral and poetic expression, it was found that the structure and composition of tyarka have repeating patterns in the old language plurality in Babar Archipelago. The plurality of old languages used and understood by the indigenous people of Southwest Maluku shows a mutually acceptable harmony of life. 1 Tulisan ini merupakan ringkasan disertasi yang berjudul â€œKesintasan Tradisi Lisan Tyarka di Kepulauan Babar, Maluku Barat Daya (2016). The structure of tyarka describes â€œtree and edgeâ€ philosophy which is its survival methaphore. As a ritual performances that are believed to be sacred, the oral tradition of tyarka have been developing significant after the formation of Southwest Maluku Regency. The endeavour to defend and inherit tyarka showed the concern and appreciation of the community toward their ancesor and its regeneration. This became a cultural force of the Babar community as an archipelago society that maintained unity and involvement.